Đáp án+Giải thích các bước giải:
Bài 1:
`a)x^3-2x^2+x`
`=x(x^2-2x+1)`
`=x(x-1)^2`
`b)x^3+4x^2+3x`
`=x(x^2+4x+3)`
`=x[(x^2+x)+(3x+3)]`
`=x[x(x+1)+3(x+1)]`
`=x(x+1)(x+3)`
`c)4x^2 y-y^3`
`=y(4x^2-y^2)`
`=y(2x-y)(2x+y)`
`d)x^3-12x^2+27x`
`=x(x^2-12x+27)`
`=x[(x^2-3x)-(9x-27)]`
`=x[x(x-3)-9(x-3)]`
`=x(x-3)(x-9)`
Bài 2:
`a)2x^2-4xy+2y^2-32`
`=2(x^2-2xy+y^2-16)`
`=2[(x-y)^2-4^2]`
`=2(x-y-4)(x-y+4)`
`b)x^2-2x+2y-xy`
`=(x^2-2x)-(xy-2y)`
`=x(x-2)-y(x-2)`
`=(x-2)(x-y)`
`c)x^2+4xy-16+4y^2`
`=(x^2+4xy+4y^2)-16`
`=(x+2y)^2-4^2`
`=(x+2y-2)(x+2y+2)`
`d)x^3-2x^2-3x+6`
`=(x^3-2x^2)-(3x-6)`
`=x^2(x-2)-3(x-2)`
`=(x-2)(x^2-3)`
Bài 3:
`a)x^2-5xy+6y^2`
`=(x^2-2xy)-(3xy-6y^2)`
`=x(x-2y)-3y(x-2y)`
`=(x-2y)(x-3y)`
`b) 4x^2-17xy+13y^2`
`=(4x^2-4xy)-(13xy-13y^2)`
`=4x(x-y)-13y(x-y)`
`=(x-y)(4x-13y)`
`c)4x^2-4xy-3y^2`
`=(4x^2+2xy)-(6xy+3y^2)`
`=2x(2x+y)-3y(2x+y)`
`=(2x+y)(2x-3y)`
`d)3x^2-8xy+4y^2`
`=(3x^2-6xy)-(2xy-4y^2)`
`=3x(x-2y)-2y(x-2y)`
`=(x-2y)(3x-2y)`
`e)x^2-21xy+38y^2`
`=(x^2-2xy)-(19xy-38y^2)`
`=x(x-2y)-19y(x-2y)`
`=(x-2y)(x-19y)`
`f)x^2+4xy-21y^2`
`=(x^2-3xy)+(7xy-21y^2)`
`=x(x-3y)+7y(x-3y)`
`=(x-3y)(x-7y)`